Top feed supplements is cheaper and sure shot reliable alternative to breastfeeding for elimination of mother to child transmission of HIV - Srivastava, Ajai Krishna; Tangri, Manoj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To find the perinatal outcome in HIV positive mothers without allowing breastfeeding. Methods: In this study all antenatal women attending our hospital OPD were screened for HIV. All HIV positive women were administered ARV prophylaxis. The method of delivery was based on the viral load in third trimester. The infants were administered NVP at birth and ZDV for six weeks. All mothers were taught the significance of infant top feeding method and were given formula feed procured by the hospital for first six months. DNA PCR screened all infants for HIV infection at 6 weeks and 6 months. They underwent HIV antibody testing by ELISA at 18 months. Results: 5701 pregnant women were screened for HIV infection from Nov 2002 to Aug 2014. 152 women were found positive for infection. 127 seropositive women delivered with us. All were administered ARV. Those who delivered with us were followed up during their pregnancy with CD4 count, viral load. All women with viral load higher than cut off women were delivered by caesarean section. All mothers were educated and provided for top feed and no children were permitted breastfeeding. They were given Nevirapine at birth and Zidovudine for 6 weeks. We found only one child positive for HIV infection out of 127 tested till the age of six months. There was no neonatal or infant mortality and significant morbidity from other infectious diseases. Conclusions: MTCT programme can lead to elimination of vertical transfer of HIV infection from mother to child even in lower socio economic class if they were provided supplementary feeds from healthcare resources along with other interventions. It is cheaper than administering ART to newborn and the mother for six months.